Improving Diabetes-Mellitus Self-Care Practice Using Educational Video in Preventing Covid-19 (EPIC-19) during the Pandemic - Sri Dewi Megayanti Mega; Inge Ruth Suantika (Babali Nursing Research, 2023)
Introduction: Diabetes is one of the comorbidities that are susceptible to infection due to chronic hyperglycemia that affects immune dysfunction, where which could be prevented by increasing self-care. Self-care is increased by providing adequate education regarding the prevention of diabetes transmission, video education is believed to help facilitate the provision of information. This study aims to determine the effect of providing educational video innovations for the prevention of covid 19 infection (EPIC-19) on the self-care of diabetic patients during the pandemic. Methods: The design of this research is a quasi-experimental design with a one-group pretest-posttest design. The population in this study were all the Diabetes with ulcers in East of Denpasar District, Denpasar Regency and number of samples was 36 respondents using a consecutive sampling according to the inclusion criteria. Collecting data using a summary diabetes self care activities (SDSCA) questionnaire modified with several statements adapted to the behavior of preventing Covid-19 infection. The Questionnaire has been validity by the face validity method from two experts in the field of endocrine academic and clinical.Data analysis using Wilcoxon test with an alpha of 0.05 Results: The results showed there was an effect of giving EPIC-19 video on respondents' self-care regarding the behavior of preventing covid 19 infection, with a p-value of 0.0001 (p <0.05). Conclusion: Video is one of the media that can be used to provide health education during a pandemic. In addition to its attractive shape, video media makes it easier for patients to understand the information needed.